Exploring the Talent Cultivation Model of Short Video Production and Operation Micro-Major in Vocational Undergraduate Programs under the New Media Environment - Yang, Yue (Education Insights, 2026)
Against the backdrop of rapid iteration in the new media industry and short videos becoming a core business of the digital economy, the market demand for compound, practical, and high-level short video production and operation talents remains strong. As an important vehicle for cultivating high-level technical and skilled talents, vocational undergraduate programs offer short video production and operation micro-majors, which is a crucial path to align with industry needs, optimize professional structure, and enhance students’ employment competitiveness. Currently, vocational undergraduate talent cultivation suffers from problems such as fragmented courses, superficial practical training, weak faculty, singular evaluation methods, and a disconnect between industry and education, making it difficult to meet the new media industry’s requirements for high-quality talent. This paper, based on the characteristics of the new media environment and the positioning of vocational undergraduate education, analyzes the job competency requirements for short video talents, constructs a micro-major talent cultivation model that integrates job training, courses, competitions, and certifications; fosters real-world learning through industry and education; implements tiered and categorized training; and empowers students with digital technology. It proposes implementation paths from six aspects: training objectives, curriculum system, practical platform, faculty, evaluation mechanism, and support system, providing theoretical reference and practical solutions for vocational undergraduate institutions to build micro-majors, deepen industry-education integration, and improve the quality of education.